2020
DOI: 10.3390/agronomy10101520
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll-a Fluorescence Analysis Reveals Differential Response of Photosynthetic Machinery in Melatonin-Treated Oat Plants Exposed to Osmotic Stress

Abstract: In this study, the effects of melatonin-induced enhancement on the principal photosynthetic parameters and antioxidant machinery were investigated in Avena sativa (oat) plants exposed to polyethylene glycol (PEG)-induced osmotic stress. The parameters of growth, chlorophyll content, stomatal conductance, proline accumulation, lipid peroxidation, and electrolyte leakage showed noteworthy improvements between the groups. Melatonin treatment caused upregulation of the genes that encode the three major antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
8
9
0
Order By: Relevance
“…The decrease of photosynthesis efficiency in plants after being exposed to adverse environmental might be a key reason for the reduction of crop. The previous studies showed abiotic stress induced irreversible damage to PSII in tomato, oat seeds, Ligustrum vicaryi and maize seedlings thereby decreasing photosynthetic rate (Ding et al, 2017;Chen et al, 2018;Alyammahi and Gururani, 2020;Kanwar et al, 2020;Yuan et al, 2020). The decrease of stomatal conductance could result in a declined P n and reduced assimilation products, thus causing an inhibited growth and a lower yield (Rao and Chaitanya, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of photosynthesis efficiency in plants after being exposed to adverse environmental might be a key reason for the reduction of crop. The previous studies showed abiotic stress induced irreversible damage to PSII in tomato, oat seeds, Ligustrum vicaryi and maize seedlings thereby decreasing photosynthetic rate (Ding et al, 2017;Chen et al, 2018;Alyammahi and Gururani, 2020;Kanwar et al, 2020;Yuan et al, 2020). The decrease of stomatal conductance could result in a declined P n and reduced assimilation products, thus causing an inhibited growth and a lower yield (Rao and Chaitanya, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, stomatal opening would improve gas exchange efficiency; as a result, this improves stress tolerance by maintaining a steady state photosynthesis [ 77 ]. It has been reported that melatonin enhances osmotic stress tolerance by promoting the efficiency of CO 2 assimilation [ 78 ] and obstructing the inhibitory effects of osmotic stress on g s [ 79 ]. Melatonin takes part in increasing g s by maintaining cell turgor that facilitates the stomatal opening and conductance [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that the stronger correlation in primed plants compared with the control was due to higher initial PI abs parallel with increase in NPQ under PEG stress. In this regard, GABA has been reported to enhance PEG-induced stress tolerance in Piper nigrum through increasing PSII activity [ 102 ], and melatonin showed to improve PI abs in oat plants exposed to PEG stress, which minimizes the inhibitory effects of PEG [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the PSII system is restricted by various environmental stresses affecting the synthesis of proteins required for its repair and proper functioning [58]. The expression of PsbA, PsB, and PsbD is repressed in oat plants under saline conditions, exhibiting damage to the PSII system [59], while 5-aminolevulinic acid application increases the PsbA and PsbD expression in wheat under drought, which represents the damage repair of the PSII system [60]. In our study, the expression levels of these genes are increased under T50 relative to the control, which indicates PSII damage repair under a low light environment.…”
Section: Discussionmentioning
confidence: 99%